Penerapan Model Pembelajaran Quiz Team Untuk Meningkatkan Motivasi Dan Hasil Belajar Materi Pemerintah Kabupaten Dan Kota Pada Siswa Kelas IV SD 4 Kaliwungu - Anik Sulistyowati (Journal Prakarsa Paedagogia, 2018)
The data obtained during the observations were carried out for students and 4th grade students of SD 4 Kaliwungu Kudus district and city education material was still low, some helped students by 35% and completeness of student learning outcomes by 29%. This is caused by the teacher still using conventional methods, students are interested in low learning. Based on the description above, the authors are interested in clearing up the research on "Application of Team Quiz Learning Models to Increase Motivation and Learning Outcomes. From research conducted and based on results and supported by data, conclusions can be drawn from the application of valuable Student Learning Quiz models to 90% and completeness of learning outcomes to 86%.